1999
DOI: 10.1038/10290
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of single-nucleotide polymorphisms in coding regions of human genes

Abstract: A major goal in human genetics is to understand the role of common genetic variants in susceptibility to common diseases. This will require characterizing the nature of gene variation in human populations, assembling an extensive catalogue of single-nucleotide polymorphisms (SNPs) in candidate genes and performing association studies for particular diseases. At present, our knowledge of human gene variation remains rudimentary. Here we describe a systematic survey of SNPs in the coding regions of human genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

95
1,029
22
20

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,565 publications
(1,166 citation statements)
references
References 29 publications
95
1,029
22
20
Order By: Relevance
“…No such trend is observed in non-coding sequences. A similar pattern was observed in genome-wide analysis of large sets of candidate genes for hypertension and other common diseases, 39,41 and in membrane transporter genes likely to play a role in drug absorption, distribution, and elimination. 30 Our results for UGT1A non-synonymous polymorphisms are consistent with this large body of data and may imply that non-coding, potentially regulatory, variants occur at higher frequencies than coding variants affecting UGT1A activity.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…No such trend is observed in non-coding sequences. A similar pattern was observed in genome-wide analysis of large sets of candidate genes for hypertension and other common diseases, 39,41 and in membrane transporter genes likely to play a role in drug absorption, distribution, and elimination. 30 Our results for UGT1A non-synonymous polymorphisms are consistent with this large body of data and may imply that non-coding, potentially regulatory, variants occur at higher frequencies than coding variants affecting UGT1A activity.…”
Section: Discussionsupporting
confidence: 72%
“…31,38 In addition, genome-wide analyses of coding polymorphisms revealed that amino-acid replacement variants tend to occur at lower frequencies compared to silent variants, consistent with the idea that non-synonymous polymorphisms tend to have deleterious effects. [39][40][41] Furthermore, investigations of specific genotype/phenotype relationships have demonstrated that rare amino-acid replacement variants with strong functional effects may significantly affect common phenotypes. 42,43 In some cases, synonymous polymorphisms also have been shown to have equally striking effects on phenotype.…”
Section: Prediction Of Functional Effects Of Amino-acid Replacement Vmentioning
confidence: 99%
“…In accordance with this prediction, Figure 2 displays the analysis of a recently updated SNP database showing that the relation of nonsynonymous (that is, more or less deleterious) SNPs to synonymous (that is, mostly neutral) SNPs increases with declining allele frequency. 12,13 Moreover, nonsense mutations appear to rise in a lower frequency interval as compared to missense mutations, fitting the expectation that, on average, nonsense mutations should be more deleterious than missense mutations and, therefore, less likely to reach higher allele frequencies.…”
Section: Frequency Distribution Of Genetic Variantsmentioning
confidence: 58%
“…Previous large-scale resequencing studies 4,5,8,9 found lower nucleotide diversity for coding regions compared to noncoding regions and decreased allele frequency for coding SNPs. These findings can be explained by the influence of purifying selection on nucleotide diversity in the human genome.…”
Section: Introductionmentioning
confidence: 80%
“…The analysis of nucleotide diversity for coding and noncoding regions in our data set (Table 1) showed estimates of p, y and Tajima's D, which were comparable with estimates from samples of European or European American origin obtained elsewhere. 4,[8][9][10] The restriction of the analysis to nonsynonymous SNPs and coding regions showed further decreased estimates for p NS , y NS and Tajima's D NS . These estimates were even lower for genomic regions coding for Pfam 11 domains or PROSITE 12 sequence motifs (Table 1).…”
Section: Nucleotide Diversity Of Sequenced Regionsmentioning
confidence: 96%